Adaptability of labor workers on hung yen province in industrial revolution 4.0 - Hoàng Thanh Xuân; Lê Văn Công (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In this paper, the author has no ambition (nor can he) fully analyze and evaluate the adaptability of workers in Hung Yen province in the trend of industrial revolution. 4.0, but would like to outline only a few adaptations of workers in Hung Yen province in the digital and digital era taking place today; on that basis, propose some recommendations to improve the adaptability of workers in the trend of industrial revolution 4.0